2020
DOI: 10.1038/s41467-020-16959-2
|View full text |Cite
|
Sign up to set email alerts
|

Widespread transcript shortening through alternative polyadenylation in secretory cell differentiation

Abstract: Most eukaryotic genes produce alternative polyadenylation (APA) isoforms. Here we report that, unlike previously characterized cell lineages, differentiation of syncytiotrophoblast (SCT), a cell type critical for hormone production and secretion during pregnancy, elicits widespread transcript shortening through APA in 3'UTRs and in introns. This global APA change is observed in multiple in vitro trophoblast differentiation models, and in single cells from placentas at different stages of pregnancy. Strikingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 70 publications
9
46
0
Order By: Relevance
“…To this end, we downloaded 10X Genomics data of placental samples (Vento-Tormo et al, 2018), which included scRNA-seq data from five donors (D8-D12). We focused on the three trophoblast cell populations we recently found to have substantial APA differences (Cheng et al, 2020), namely, villous cytotrophoblasts (VCTs), extravillous trophoblasts (EVTs) and syncytiotrophoblasts (SCTs) (Figures 4A and S9). Because VCTs are the precursor cells of the other two subtypes (Chang et al, 2018), we compared APA profiles of EVTs of SCTs with those of VCTs.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we downloaded 10X Genomics data of placental samples (Vento-Tormo et al, 2018), which included scRNA-seq data from five donors (D8-D12). We focused on the three trophoblast cell populations we recently found to have substantial APA differences (Cheng et al, 2020), namely, villous cytotrophoblasts (VCTs), extravillous trophoblasts (EVTs) and syncytiotrophoblasts (SCTs) (Figures 4A and S9). Because VCTs are the precursor cells of the other two subtypes (Chang et al, 2018), we compared APA profiles of EVTs of SCTs with those of VCTs.…”
Section: Resultsmentioning
confidence: 99%
“…There is now accumulating evidence that Rbm24 performs post-transcriptional functions in the cytoplasmic compartment of different cell types entered into the differentiation program. Indeed, our recent studies showed that both mouse and zebrafish Rbm24 is localized in the cytoplasm of differentiating cells in the head sensory organs to regulate mRNA stability and cytoplasmic polyadenylation 30,47,48 . This raises an interesting possibility that Rbm24 may also regulate the poly(A) tail length and thus the translational efficiency of muscle-specific mRNAs during early stages of muscle development and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…S ignificance A nalysis of A lternative P olyadenylation using R NA- S eq ( SAAP-RS ) [ 111 ] uses RNA-seq samples from bulk, single cell and 3 focused (e.g., 3 READS+ [ 10 ]) approaches to identify APA events. The method calculates RNA-seq read counts upstream (UP) and downstream (DN) of every poly(A) site identified from PolyA_DB3 database and performs a statistical test to derive a p-value to compare the read distribution in UP and DN regions between two samples.…”
Section: Bioinformatic Methods For Detection Of Poly(a) Sitesmentioning
confidence: 99%
“…Most scRNA-seq methods use 3 tag-based approach to generate reads enriched at 3 ends of mRNA similar to the approaches described above ( Table 1 ). Several laboratories have already turned to scRNA-seq to study complex APA regulatory patterns in tissues and organs [ 10 , 81 , 82 , 83 ].…”
Section: Next-generation Sequencing Based Techniques For Characterisation Of Apamentioning
confidence: 99%
See 1 more Smart Citation